Feeding ecology, reproductive biology, and parasitism of gymnodactylus geckoides spix, 1825 from a caatinga area in northeastern Brazil - de Alcantara, Edna Paulino [UNESP]; Ferreira-Silva, Cristiana [UNESP]; Gonçalves-Sousa, José Guilherme; Morais, Drausio Honorio; Ávila, Robson Waldemar (My University, 2019)
Neotropical lizards belonging to the genus Gymnodactylus are endemic to South America, occurring in the Caatinga, Cerrado and Atlantic Forests in Brazil. We collected specimens of the Naked-toed Gecko (Gymnodactylus geckoides) using pitfall traps and Time Constrained Searches in two areas of Caatinga and studied diet, reproduction, sexual dimorphism, and parasite burden. Gymnodactylus geckoides has continuous reproduction and sexual dimorphism. The species is a dietary generalist and preyed on invertebrates, mainly Orthoptera and Aranae and Isopoda, and had a low parasite richness.
Keywords: Diet; Helminth; Naked-toed Gecko; Reproductive; Sexual dimorphism